Peran Pendidikan Vokasional dalam Mendorong Praktik Pertanian Berkelanjutan: Studi Deskriptif di Komunitas Pedesaan Natar, Kabupaten Lampung Selatan - Citra Rianzani; Suci Amalia; Akmal Attamimi; Sa’idy, Sa’idy (CV. Creative Tugu Pena, 2021)
This study aims to examine respondents' perceptions of various aspects of vocational education in supporting community skill development. The research involved seven key variables: skill-based curriculum, availability of training facilities, quality of instructors, practical and applicable learning methods, internship or field practice programs, collaboration with local stakeholders, and alignment of training with local needs. The results show that the majority of respondents rated the quality of instructors (93.3%), practical learning methods (86.7%), and training relevance to local needs (83.3%) as good. However, lower satisfaction was found in the availability of training facilities (60.0%), internship programs (60.0%), and stakeholder collaboration (66.7%). These findings indicate that vocational education has a positive impact on enhancing local human resources, but improvements are still needed in infrastructure and partnerships with the industry to increase its effectiveness and sustainability.